Age-Related Differences in Emoji Evaluation. Issue 5 (19th October 2020) - Weiß, Martin; Bille, Dariana; Rodrigues, Johannes; Hewig, Johannes
ABSTRACT: Background: For decades, the nature of emotions has been at the center of psychological research, particularly regarding the underlying mechanisms that enable people to perceive, recognize, and process emotional stimuli. Research has indicated that there are interindividual differences in the processing of emotions. This includes age, which underlies neurological changes that contribute to the specific processing of emotions. Increasing age seems to be associated with a more positive evaluation of emotional information, from perception itself to attention, memory, and decision-making. Method: The current study aimed to investigate whether these differences can be found in highly artificial emotional faces. Since emojis are representatives of emotional faces in digital communication, we selected a subset of 13 emojis and asked 170 participants to evaluate them for their ability to represent different target emotions. Results: An exploratory factor analysis revealed a two-factorial structure with positive and negative valence for most of the ratings for the evaluated emojis. Furthermore, a multilevel model analysis based on the individual factor scores indicated higher age to be associated with an increase in factor scores for negative valence compared to positive valence. Conclusion: In the present study, a trend for an age-specific positivity bias could only be shown in the classical smiley, while other emojis were related to negative valence with increasing age. Thus, we revealed age-related differences in emotion classification, even for highly artificial stimuli such as emojis.